Upaya Peningkatan Pengetahuan tentang Perilaku Hidup Bersih dan Sehat untuk Menciptakan Generasi Peduli Sehat pada Anak di SD Negeri 1 Laangke - Sumi, Susi Sastika; Y, Yusnaeni; Nurafriani; Sugarni, Mika (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Clean and healthy living behavior is a behavior that must be carried out based on the awareness of the individual himself, this awareness arises if he has knowledge about what he will do. The purpose of this community service is to provide health education to school-age children about clean and healthy living behavior, in order to create a healthy caring generation at SD Negeri 1 Laangke. The target of this community service is students. Community service is carried out for 1 day. The methods used are pretest, education, and posttest. The Pre Test is carried out to determine the initial knowledge of students about clean and healthy living behavior. Then education is carried out about clean and healthy living behavior that is applied in everyday life in the school environment and in the home environment where each person lives. After that, a Post Test is carried out. The Post Test is carried out to determine the results of education about clean and healthy living behavior in children in order to create a healthy caring generation.